Konsep Tafakur untuk Penguatan Efikasi Diri pada Pribadi Introvert - Mirsanti, Nining (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2019)
Since man was born he has been given various natural potentials or in Islam called fitrah. The task of man is to develop that nature so that it runs according to its nature. In reality it can be found various individuals with a degree of difficulty to develop their nature, such as introverted individuals, one of the causes of whichis low self-efficacy. Therefore, the concept of tafakur is needed. The type of research used in this article is library research and the nature of this research is qualitative descriptive. The concept of tafakur is present to direct individuals to Islamic concepts to see that all the realities of their lives are optimistically good that the process of adjusting themselves to the environment will be even better, because tafakur is an activity carried out by humans to present the world as a model and effectively treat it according to its purpose and how to deal with a problem by taking lessons behind the problem at hand, so that it does not cause conflict or conflict in itself which is understood as intrapersonal communication by understanding and providing solutions to itself that there are still many shortcomings in the individual, so the concept of tafakur will very useful for improving introverted personal self-efficacy.